Respuesta :

Answer:

Step-by-step explanation:

a. 5(x+4) + 2(x+3)  = 5*x + 5*4 + 2*x + 2*3

                             = 5x + 20 + 2x + 6  

                            = 5x + 2x + 20 +6  {bring like terms together}

                            = 7x + 26

b. 3(y+6) + 4(y-5)​ = 3*y + 3*6 + 4*y - 4*5

                           = 3y + 18 + 4y - 20  

                           = 3y + 4y + 18 - 20   {bring like terms together}

                          = 7y - 2

Answer:

a. 7x+26

b.7y-2

Step-by-step explanation:

for question a

1.Do 5 multiplied by x (5x) and 5 multiplied by 4 (20) and do the same with the other brackets

2. simplify the expression (collect the like terms)

5x+20+2x+6=6x+26

3.calculate the sum

DO THE SAME FOR QUESTION b

ACCESS MORE